Development and effects of MY-IPV educational module on perceptions and attitudes towards intimate partner violence among premarital young adults in Kelantan - Hazaha, Hanin Syahira (2023)
An individual in an intimate relationship may experience offensive treatment by their partner. This could also happen to young adults who are in a stage to build a concrete relationship and prepare for marriage. This study aimed to develop an educational module and assess its effectiveness on perceptions and attitudes towards intimate partner violence (IPV) among premarital young adults in Kelantan. It was conducted in two phases. Phase One involved the development and validation of an educational module on IPV (my-IPV educational module), while Phase Two was a randomized controlled trial (RCT). The first step in Phase One was a needs assessment study, and it ended with testing of the newly developed module for content validation among six experts and face validation among 30 young adults. Phase Two involved the registered participants of premarital courses under Religious District Offices in four randomly selected districts in Kelantan. A total of 74 participants were assigned into the intervention and control groups. The intervention group received e-book, presentation slides, video, and infographic messages which were delivered through WhatsApp at Month 0 and Month 1. Measurements of perceptions and attitudes towards IPV were done at baseline and Month 2. The Repeated Measures Analysis of Variance (RM-ANOVA) was used to determine the effectiveness of the intervention. The dependent variable was the scores of perceptions and attitudes towards IPV, while the independent variable was intervention or control group. All the six experts rated the my-IPV educational module as valid (I-CVI 1.00). The 30 young adults also agreed with the literary presentation, understandability, as well as quality of information and illustrations of the materials. The module was tested among 33 participants in intervention group and 35 participants in control group who completed the follow-up until two months. The mean age of participants in intervention group was 24.36 (2.86) and control group was 24.37 (2.76) years. There were no significant differences in the sociodemographic and relationship characteristics between the groups. The RM ANOVA test statistics showed significant increment in mean score of perceptions from pre to post period in the intervention group, with Pillai’s Trace [F-stat(df) = 24.27(1,66), p-value <0.001]. However, there was no significant increment in mean score of perceptions for control group (p=0.450). There was also a significant mean difference in perceptions score between the control and intervention groups after the intervention period (post), p-value=0.001. As for attitudes, there was no significant increase in the mean attitudes score from pre- to post-intervention in the intervention group, with Pillai’s Trace [F-stat (df) = 2.77(1,66), p-value =0.101.], and control group, with Pillai’s Trace [F-stat (df) = 0.042(1,66), p-value =0.838]. There was also no significant difference in mean score of attitudes towards IPV between the intervention and control groups with regards to time with Pillai’s Trace [F-stat (df) = 1.79 (1,66), p-value 0.297]. The my-IPV educational module is effective in increasing perceptions towards IPV, but not attitudes. Other factors need to be considered to explain and improve the effect on attitudes towards IPV among young adults.